Osteopathic Manipulative Treatment in Improving Health Related Quality of Life in a Patient with Gastroesophageal Reflux Disease: A Case Report - Manu Goyal; Udit Narang; Sonakshi Sehgal (Dr. Annil Mahajan, 2021)
The case report presents a 30-year-old female, diagnosed as GERD, and presented with the complaints of pain and burning feeling behind the breastbone, and a wave of burning heat travelling momentarily from epigastric. OMT was given once/week for 4 weeks. Health-related quality of life scale for gastroesophageal reflux disease (HRQL-GERD), quality of life scale (QS-GERD) Symptom score, 24 hr. esophageal pH metry, DeMeester was measured at baseline, 4th week post OMT and 2nd week follow-up. The application of OMT reduced the symptoms and improved, 24 hr. esophageal pH metry, DeMeester score and HRQL-GERD andQS-GERD Symptom score.